PARTICIPATION IN THE 2024 LEGISLATIVE ELECTION FOR THE REGIONAL PEOPLE'S REPRESENTATIVE COUNCIL OF DAPIL 5, DONGGALA REGENCY - Umi Farida Rohmah; Irwan Waris; M Nur Alamsyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Voter participation constitutes a fundamental dimension of democratic governance, particularly within legislative elections that shape policy-making at the regional level. This study examines voter participation in the 2024 legislative election for the Regional House of Representatives (DPRD) in Electoral District 5 of Donggala Regency, Indonesia. Employing a qualitative descriptive research design, the study draws on in-depth interviews, non-participant observation, and analysis of official electoral documents to explore the patterns and determinants of electoral participation. The findings reveal that while voter turnout in the district remained relatively stable, participation was predominantly procedural rather than substantive. Many voters engaged in the electoral process without sufficient understanding of legislative functions, candidate programs, or policy implications. Voter participation was strongly influenced by political literacy, candidate-centered mobilization strategies, socioeconomic considerations, and the quality of electoral administration. Furthermore, the simultaneous conduct of elections in 2024 contributed to reduced voter attention toward legislative contests, thereby limiting meaningful engagement. The study concludes that voter participation in Electoral District 5 reflects broader challenges of local democratic consolidation in Indonesia, where formal participation persists amid weak deliberative quality. Strengthening civic education, improving party institutionalization, and enhancing the responsiveness of local legislative institutions are essential to fostering more informed and substantive voter participation in future elections.